Perkembangan Gereja Awal (Kisah Para Rasul 1 : 8) Jejak Misi yang Mengubah Dunia - Desti Meliana Mangngi Kale; Malik Bambangan (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
Acts 1:8 became an important foundation for the mission of the early church to function as an agent of change in the world. In this verse, Jesus calls his disciples to be His witnesses in various regions, from Jerusalem to the ends of the earth, while emphasizing the importance of cross-cultural missions in the development of the church. The method used is descriptive qualitative with a biblical approach. sThe rapid spread of the Gospel reflects the universal appeal of Christ's message that transcends cultural and geographical boundaries, and its relevance for all people. Thus, the mission of the early church not only changed the spiritual lives of individuals, but also had a significant social impact, including strengthening communities, caring for the poor, and defending human rights. The results of this article review show an answer that mission is not just the task of a few people, but is the collective responsibility of all believers to create a better and more just world, in accordance with the teachings of Christ.